KAJIAN DAMPAK USAHA BUDIDAYA IKAN PATIN JAMBAL (Pangasius djambal) SISTEM KARAMBA TERHADAP KUALITAS AIR SUNGAI OGAN KECAMATAN PEMULUTAN BARAT KABUPATEN OGAN ILIR - EKA CHANDRA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2008)
This current research aimed to know the influence of floating cage density on water quality of Ogan River for fishery activity at West Pemulutan, Sub District.Method applied in this research was survey method. River characteristics and water quality variables observed namely: the depth of river, river width, water transparance, pH and water temperature were measured directly in the field. Other variables such as carbondioxide, nitrite, nitrate, ammonia, dissolved oxygen (DO) and TOM were measured in the laboratory. The Determination of sample location was determined based on the total of floating cage, namely: without floating cage (up-stream), the highest density of floating cage (Sukamerindu), the high density floating cage (Kamal), the low density floating cage (Talang Pangeran), without floating cage (down-stream). Amount of samples was 5 - 10 % of floating cages and determined based on stratification sampling procedure. Result showed that the water quality status of Ogan River determined based on STORET method was slightly contaminated in all five locations. Ammonia yielded from floating cage activities (feeding and metabolism) polluted Ogan River water. The ammonia concentration increased as floating cage density increased